IMPLEMENTATION OF A RESTORATIVE APPROACH IN CHILD CRIMINAL RESCUE IN JUSTICE - Fikri, Rahul Ardian; Siregar, Abdul Rahman Maulana; Rafianti, Fitri; Mawarni, Senja (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This study aims to discuss diversion policies in restorative justice for the Criminal Justice System faced by minors. Where it is known that diversion is not a reconciliation between children in conflict with the law and victims or their families, but must be a form of punishment against children who are in conflict with the law in an informal way. The recommendation in this study is that law enforcers in carrying out their duties of investigation, prosecution, investigation and determination of cases by the court should prioritize the application of diversion policies as an alternative to imprisonment or imprisonment. Massive socialization of this diversion policy to the public is urgently needed.